Supplement to Inductive Logic

Appendix 3: Derivations of the Two Bayesian Estimation Rules, Rule BE-D and Rule BE-C

We restate each rule, BE-D and BE-C, and provide proofs of their claims along the way.

Rule BE-D: Bayesian Estimation for Disjunctions of Alternative Hypotheses

Let \(H\) be a collection of \(z\) alternative hypotheses, \(z \ge 2\), where the conjunction of any two of them is logically inconsistent. Let \(c\) be observational or experimental conditions for which \(e\) describes one of the possible outcomes. And suppose \(b\) is a conjunction of relevant auxiliary hypotheses and plausibility considerations. For each hypothesis \(h\) in \(H\), let its prior probability be non-zero: \(P[h \mid c \cdot b] \gt 0\).

Choose any \(k\) hypotheses from collection \(H\), where each one of them, \(h\), has a likelihood value \(P[e \mid h \cdot c \cdot b] > 0\). Label these \(k\) hypotheses (in whatever order you wish) as \(\lsq h_1\rsq\), \(\lsq h_2\rsq\), …, \(\lsq h_k\rsq\). Then label all the remaining hypotheses in \(H\) (in whatever order you wish) as \(\lsq h_{k+1}\rsq\), \(\lsq h_{k+2}\rsq\), …, \(\lsq h_z\rsq\).

Given these labelings of hypotheses in \(H\), let \((h_1 \vee \ldots \vee h_k)\) represent the disjunction of the first \(k\) hypotheses chosen from \(H\), and \((h_{k+1} \vee \ldots \vee h_z)\) represent the disjunction of the remaining hypotheses from \(H\). The expression \((h_1 \vee \ldots \vee h_z)\) represents the disjunction of all hypotheses in \(H\). Furthermore, let \(b\) logically entail this disjunction of all alternative hypotheses in \(H\): \(b \vDash (h_1 \vee \ldots \vee h_z)\). So, both \(P[(h_1 \vee \ldots \vee h_z) \mid c \cdot b] = 1\) and \(P[(h_1 \vee \ldots \vee h_z) \mid c \cdot e \cdot b] = 1\).

Then, the posterior probability of \((h_1 \vee \ldots \vee h_k)\) satisfies the following form of Bayes’ Theorem:

\[ P[(h_1 \vee \ldots \vee h_k) \mid c \cdot e \cdot b] \; \; = \; \; \frac{\sum_{j = 1}^k P[e \mid h_j \cdot c \cdot b] \times P[h_j \mid c \cdot b]}{\sum_{i = 1}^z P[e \mid h_i \cdot c \cdot b] \times P[h_i \mid c \cdot b]}. \]

Proof:

Since \(P[(h_1 \vee \ldots \vee h_z) \mid c \cdot e \cdot b] = 1\), we have

\[\begin{align} &P[(h_1 \vee \ldots \vee h_k) \mid c \cdot e \cdot b] \\ &\qquad = \frac{P[(h_1 \vee \ldots \vee h_k) \mid c \cdot e \cdot b]}{P[(h_1 \vee \ldots \vee h_z) \mid c \cdot e \cdot b]} \\ &\qquad = \frac{\sum_{j = 1}^k P[h_j \mid c \cdot e \cdot b]}{\sum_{i = 1}^z P[h_i \mid c \cdot e \cdot b]} \\ &\qquad = \frac{\sum_{j = 1}^k P[h_j \mid c \cdot e \cdot b] \times P[e \mid c \cdot b]}{\sum_{i = 1}^z P[h_i \mid c \cdot e \cdot b] \times P[e \mid c \cdot b]} \\ &\qquad = \frac{\sum_{j = 1}^k P[h_j \cdot e \mid c \cdot b]}{\sum_{i = 1}^z P[h_i \cdot e \mid c \cdot b]} \\ &\qquad = \frac{\sum_{j = 1}^k P[e \mid h_j \cdot c \cdot b] \times P[h_j \mid c \cdot b]}{\sum_{i = 1}^z P[e \mid h_i \cdot c \cdot b] \times P[h_i \mid c \cdot b]}. \end{align}\]

In cases where the values of all the prior probabilities, \(P[h_i \mid c \cdot b]\), are known, or can be closely approximated, this equation suffices to provide values for the argument strengths \(r\) of the posterior probabilities, \(P[(h_1 \vee \ldots \vee h_k) \mid c \cdot e \cdot b] = r\). But when no precise values of the priors are available, a useful estimate of bounds on the posterior probabilities may be derived as follows.

Let \(K\) be (your best estimate of) an upper bound on the ratios of prior probabilities, \(P[h_i \mid c \cdot b] / P[h_j \mid c \cdot b]\) for all \(h_j\) in \(\{h_1, h_2, \ldots, h_k\}\) and all \(h_i\) in \(\{h_{k+1}, h_{k+2}, \ldots, h_z\}\). That is, for whichever \(h_j\) in \(\{h_1, h_2, \ldots, h_k\}\) has the smallest value of \(P[h_j \mid c \cdot b]\), and for whichever \(h_i\) in \(\{h_{k+1}, h_{k+2}, \ldots, h_z\}\) has the largest value of \(P[h_i \mid c \cdot b]\), let \(K\) be a real number that is large enough that \(K \ge P[h_i \mid c \cdot b] / P[h_j \mid c \cdot b]\).

Then, \[ \Omega[\neg (h_1 \vee \ldots \vee h_k) \mid c \cdot e \cdot b] \; \; \le \; \; K \times \left[\frac{1}{\frac{\sum_{j = 1}^k P[e \;\mid\; h_j \cdot c \cdot b]}{\sum_{i = 1}^z P[e \;\mid\; h_i \cdot c \cdot b]}} - 1 \right]. \]

Proof:

\[\begin{align} &\Omega[\neg (h_1 \vee \ldots \vee h_k) \mid c \cdot e \cdot b] \\ &\quad = \frac{P[(h_{k+1} \vee \ldots \vee h_z) \mid c \cdot e \cdot b]}{P[(h_1 \vee \ldots \vee h_k) \mid c \cdot e \cdot b]} \\ &\quad = \frac{\sum_{i = k+1}^z P[e \mid h_i \cdot c \cdot b] \times P[h_i \mid c \cdot b]}{\sum_{j = 1}^k P[e \mid h_j \cdot c \cdot b] \times P[h_j \mid c \cdot b]} \\ &\quad \le K \times \frac{\sum_{i = k+1}^z P[e \mid h_i \cdot c \cdot b]}{\sum_{j = 1}^k P[e \mid h_j \cdot c \cdot b]} \\ &\quad = K \times \left[\frac{\sum_{i = k+1}^z P[e \mid h_i \cdot c \cdot b] + \sum_{j = 1}^k P[e \mid h_j \cdot c \cdot b]}{\sum_{j = 1}^k P[e \mid h_j \cdot c \cdot b]} - 1\right] \\ &\quad = K \times \left[\frac{\sum_{i = 1}^z P[e \mid h_i \cdot c \cdot b]}{\sum_{j = 1}^k P[e \mid h_j \cdot c \cdot b]} - 1\right] \\ &\quad = K \times \left[\frac{1}{\frac{\sum_{j = 1}^k P[e \;\mid\; h_j \cdot c \cdot b]}{\sum_{i = 1}^z P[e \;\mid\; h_i \cdot c \cdot b]}} - 1 \right]. \end{align}\]
Thus, a lower bound on the associated posterior probability of \((h_1 \vee \ldots \vee h_k)\) is given by the formula \[\begin{align} P[(h_1 \vee \ldots \vee h_k) \mid c \cdot e \cdot b] \; \; &= \; \; \frac{1}{1 + \Omega[\neg (h_1 \vee \ldots \vee h_k) \mid c \cdot e \cdot b]} \\ &\ge \; \; \frac{1}{1 + K \times \left[\frac{1}{\frac{\sum_{j = 1}^k P[e \;\mid\; h_j \cdot c \cdot b]}{\sum_{i = 1}^z P[e \;\mid\; h_i \cdot c \cdot b]}} - 1 \right]}. \end{align}\]

Rule BE-C: Bayesian Estimation for a Continuous Range of Alternative Hypotheses

Let \(H\) be a continuous region of alternative hypotheses \(h_q\), where \(q\) is a real number, and where the conjunction of any two of these hypotheses is logically inconsistent. Let \(c\) be observational or experimental conditions for which \(e\) describes one of the possible outcomes. And suppose \(b\) is a conjunction of relevant auxiliary hypotheses and plausibility considerations. For each point hypothesis \(h_q\) in \(H\), we take \(p[e \mid h_q \cdot c \cdot b]\) to be an appropriate likelihood.

Let \(p[h_q \mid c \cdot b]\) and \(p[h_q \mid c \cdot e \cdot b]\) be probability density functions on \(H\), where these two density functions are related as follows: \[p[h_q \mid c \cdot e \cdot b] \times P[e \mid c \cdot b] \;=\; p[e \mid h_q \cdot c \cdot b] \times p[h_q \mid c \cdot b].\]

We suppose throughout that prior probability density \(p[h_q \mid c \cdot b] > 0\) for all values of \(q\).

The prior probability that the true point hypothesis \(h_r\) lies within measurable region \(R\) is given by

\[\begin{align} P[h_R \mid c \cdot b] \; &= \; \int_R p[h_r \mid c \cdot b] \; dr,\;\; \text{where} \\ P[h_H \mid c \cdot b] \; &= \; \int_H p[h_q \mid c \cdot b] \; dq \: =\: 1. \end{align}\]

The posterior probability that the true point hypothesis \(h_r\) lies within measurable region \(R\) is given by

\[\begin{align} P[h_R \mid c \cdot e \cdot b] \; &= \; \int_R p[h_r \mid c \cdot e \cdot b] \; dr, \;\; \text{where} \\ P[h_H \mid c \cdot e \cdot b] \; &= \; \int_H p[h_q \mid c \cdot e \cdot b] \; dq \: =\: 1. \end{align}\]

Then, the posterior probability satisfies the following equation for each measurable region \(R\): \[ P[h_R \mid c \cdot e \cdot b] = \frac{\int_R p[e \mid h_r \cdot c \cdot b] \times p[h_r \mid c \cdot b] \; \; dr}{\int_H p[e \mid h_q \cdot c \cdot b] \times p[h_q \mid c \cdot b] \; \; dq}. \]

Proof:

Since \(P[h_H \mid c \cdot e \cdot b] = 1\), we have

\[\begin{align} P[h_R \mid c \cdot e \cdot b] \; &= \; \frac{P[h_R \mid c \cdot e \cdot b]}{P[h_H \mid c \cdot e \cdot b]} \\ &= \; \frac{\int_R p[h_R \mid c \cdot e \cdot b] \; \; dr}{\int_H p[h_q \mid c \cdot e \cdot b] \; \; dq} \\ &= \; \frac{\int_R p[h_R \mid c \cdot e \cdot b] \times P[e \mid c \cdot b] \; \; dr}{\int_H p[h_q \mid c \cdot e \cdot b] \times P[e \mid c \cdot b] \; \; dq} \\ &= \; \frac{\int_R p[e \mid h_r \cdot c \cdot b] \times p[h_r \mid c \cdot b] \; \; dr}{\int_H p[e \mid h_q \cdot c \cdot b] \times p[h_q \mid c \cdot b] \; \; dq} \end{align}\]

In cases where a precise model of the prior probability density, \(p[h_q \mid c \cdot b]\), is available, this equation suffices to provide values for the posterior probabilities, \(P[h_R \mid c \cdot e \cdot b]\). However, when no precise model of the priors is available, bounds on the values of posterior probabilities may be evaluated in the following way.

Let \(K\) be (your best estimate of) an upper bound on the ratios of the probability density values, \(p[h_q \mid c \cdot b] / p[h_r \mid c \cdot b]\), for each \(h_r\) in region \(R\) and \(h_q\) in \((H-R)\). That is, for whichever \(h_r\) in \(R\) has the smallest value of \(p[h_r \mid c \cdot b]\), and for whichever \(h_q\) in \((H-R)\) has the largest value of \(p[h_q \mid c \cdot b]\), let \(K\) be a real number such that \(K \ge p[h_q \mid c \cdot b] / p[h_r \mid c \cdot b]\).

Then, \[ \Omega[\neg h_R \mid c \cdot e \cdot b] \; \; \le \; \; K \times \left[\frac{1}{\frac{\int_{R} p[e \;\mid\; h_r \cdot c \cdot b] \; \; dr}{\int_{H} p[e \;\mid\; h_q \cdot c \cdot b] \; \; dq}} - 1 \right]. \]

Proof:

\[\begin{align} &\Omega[\neg h_R \mid c \cdot e \cdot b] \\ &\quad = \frac{P[h_{H-R} \mid c \cdot e \cdot b]}{P[h_R \mid c \cdot e \cdot b]} \\ &\quad = \frac{\int_{H-R} p[h_q \mid c \cdot e \cdot b] \; \; dq}{\int_{R} p[h_r \mid c \cdot e \cdot b] \; \; dr} \\ &\quad = \frac{\int_{H-R} p[h_q \mid c \cdot e \cdot b] \times P[e \mid c \cdot b] \; \; dq}{\int_{R} p[h_r \mid c \cdot e \cdot b] \times P[e \mid c \cdot b] \; \; dr}\\ &\quad = \frac{\int_{H-R} p[e \mid h_q \cdot c \cdot b] \times p[h_q \mid c \cdot b] \; \; dq}{\int_{R} p[e \mid h_r \cdot c \cdot b] \times p[h_r \mid c \cdot b] \; \; dr}\\ &\quad \le K \times \frac{\int_{H-R} p[e \mid h_q \cdot c \cdot b] \; \; dq}{\int_{R} p[e \mid h_r \cdot c \cdot b] \; \; dr} \\ &\quad = K \times \left[\frac{\int_{H-R} p[e \mid h_q \cdot c \cdot b] \; \; dq \;\; + \;\; \int_{R} p[e \mid h_r \cdot c \cdot b] \; \; dr}{\int_{R} p[e \mid h_r \cdot c \cdot b] \; \; dr} - 1 \right] \\ &\quad = K \times \left[\frac{\int_{H} p[e \mid h_q \cdot c \cdot b] \; \; dq}{\int_{R} p[e \mid h_r \cdot c \cdot b] \; \; dr} - 1 \right] \\ &\quad = K \times \left[\frac{1}{\frac{\int_{R} p[e \;\mid\; h_r \cdot c \cdot b] \; \; dr}{\int_{H} p[e \;\mid\; h_q \cdot c \cdot b] \; \; dq}} - 1 \right]. \end{align}\]

Thus, a lower bound on the associated posterior probability of \(h_R\) is given by the formula

\[\begin{align} P[h_R \mid c \cdot e \cdot b] \;\; &= \;\; \frac{1}{1 + \Omega[\neg h_R \mid c \cdot e \cdot b]} \\ &\ge \; \; \frac{1}{1 + K \times \left[\frac{1}{\frac{\int_{R} \; p[e \;\mid\; h_r \;\cdot\; c \cdot b] \; \; dr}{\int_{H} \; p[e \;\mid\; h_q \cdot c \cdot b] \; \; dq}} - 1 \right]}. \end{align}\]

Copyright © 2025 by
James Hawthorne <hawthorne@ou.edu>

Open access to the SEP is made possible by a world-wide funding initiative.
The Encyclopedia Now Needs Your Support
Please Read How You Can Help Keep the Encyclopedia Free